2018
DOI: 10.1093/humrep/dey046
|View full text |Cite
|
Sign up to set email alerts
|

Why are there more same-sex than opposite-sex dizygotic twins?

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Our twin sample showed a MZ:DZ ratio of around 1:1, which is unbalanced as compared to the 1:2 ratio observed in the general population (Aston et al, 2008). This situation is consistent with the fact that, although twin cohorts in the Italian Twin Registry (ITR) are identified by applying a population-based strategy within local municipalities (Medda et al, 2019), subjects’ participation in ITR studies still relies on a strong voluntary basis, and it has been previously reported that MZ twins are likely to be over-represented in volunteer samples (Kanazawa et al, 2018; Rushton et al, 2008). In this respect, it may also be interesting to highlight that a MZ:DZ ratio close to 1:1 may even have, in some cases, beneficial effects on statistical power in the context of twin analyses (Visscher, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…Our twin sample showed a MZ:DZ ratio of around 1:1, which is unbalanced as compared to the 1:2 ratio observed in the general population (Aston et al, 2008). This situation is consistent with the fact that, although twin cohorts in the Italian Twin Registry (ITR) are identified by applying a population-based strategy within local municipalities (Medda et al, 2019), subjects’ participation in ITR studies still relies on a strong voluntary basis, and it has been previously reported that MZ twins are likely to be over-represented in volunteer samples (Kanazawa et al, 2018; Rushton et al, 2008). In this respect, it may also be interesting to highlight that a MZ:DZ ratio close to 1:1 may even have, in some cases, beneficial effects on statistical power in the context of twin analyses (Visscher, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…This is not consistent with Weinberg's differential rule, which states that DZ twins are equally likely to be of the same or opposite sex [15]. Possible explanations for this discrepancy are that the CNTR is not a birth registry or that real-world data may deviate from this assumption of independence of sexes within DZ twin pairs [16].…”
Section: Zygosity Determinationmentioning
confidence: 62%
“…1 Among the total dizygotic twins, approximately 40% are opposite-sex (OS). 2 Androgens, particularly testosterone, serve important functions in early embryonic development. 3 Testosterone production in fetuses increases from 8 to 24 weeks of gestation and reaches maximal level between 10 and 15 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of spontaneous dizygotic twinning occurs between 1% and 4%, which might be increased by advanced maternal age and the application of assisted reproductive technologies 1 . Among the total dizygotic twins, approximately 40% are opposite‐sex (OS) 2 …”
Section: Introductionmentioning
confidence: 99%